Discovery of Antimycin-Type Depsipeptides from a wbl Gene Mutant Strain of Deepsea-Derived Streptomyces somaliensis SCSIO ZH66 and Their Effects on Pro-inflammatory Cytokine Production - Li, Huayue; Huang, Huiming; Hou, Lukuan; Ju, Jianhua; Li, Wenli (Frontiers in Microbiology, 2017)
Deepsea microbes are a rich source of novel bioactive compounds, which have developed unique genetic systems as well as biosynthetic pathways compared with those of terrestrial microbes in order to survive in extreme living environment. However, a large variety of deepsea-microbial secondary metabolic pathways remain “cryptic” under the normal laboratory conditions. Manipulation of global regulators is one of the effective approaches for triggering the production of cryptic secondary metabolites. In this study, by combination of various chromatographic purification process, we obtained somalimycin (1), a new antimycin-type depsipeptide, with an unusual substitution of 3-aminosalicylate instead of conserved 3-formamidosalicylate moiety, along with two known (2 and 3) analogs from the ΔwblAso mutant strain of deepsea-derived Streptomyces somaliensis SCSIO ZH66. The structures of 1–3 were elucidated on the basis of extensive spectroscopic analyses including LC-MS and NMR. In the evaluation of potent anti-inflammatory activity, compound 2 exhibited strong inhibitory activity on the IL-5 production in ovalbumin-stimulated splenocytes with IC50 value of 0.57 μM, while 1 and 3 displayed mild effect (>10 μM), which might be attributed to their different side-chain substitutions. Moreover, compounds 1–3 showed very weak cytotoxicity against human umbilical vein endothelial cells with LD50 values of 62.6, 34.6, and 192.9 μM, respectively, which were far over their IL-5 inhibitory activity. These results indicated that these compounds have good potential for further use in anti-inflammatory drug development.